Surgical management of oral cancer extending to the pterygoid region - Yu-Wei Chiu, DDS, MDS; Pei-Yin Chen, DDS; Yi-Tzu Chen, DDS, MDS; Cheng-Chieh Yang, DDS, PhD (Elsevier, 2021)
The resection of oral cancers extending into the pterygoid region remain a challenge for head and neck surgeons. Few studies have suggested the approach methods and showed that the tumor can be resected with a clear vision. In this case series study, we advocated a surgical method for the tumor ablation surgery over this region. The study was conducted in 11 patients with tumors near or directly invading into the pterygoid regions. A cheek flap combined with ramus removal was used to approach the pterygoid plates and the associated muscles. A reciprocating saw was used subsequently for the pterygoid plate resection. In the collected 11 patients, neither serious complications occurred during the surgery nor immediate complications happened after the surgery. Four patients expired during the postoperative follow-up period. Two of them died of cancer related conditions, one for tumor recurrence and the other for distant metastasis. The reasons for non-cancer specific mortality were myocardial infraction and aspiration pneumonia Only one patient showed positive margins in the final surgical pathology.